2021
DOI: 10.1007/s13337-021-00710-6
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Covid 19 have significantly reduced CH50 activity

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which causes coronavirus disease 2019 (COVID-19), is a new virus that emerged in China and immediately spread around the world. Evidence has been documented that the immune system is impressively involved in the pathogenesis of this disease, especially in causing inflammation. One of the important components of the immune system is the complement system whose increased activity has been shown in inflammatory diseases and consequently damage caused b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
(40 reference statements)
2
5
0
Order By: Relevance
“…The finding also match earlier findings by Ghazavi et al, which showed that C3 and C4 levels were markedly decreased in severe COVID-19 patients in comparison with non-severe COVID-19 patients [8]. In agreement with our data, Keshavarz et al indicated that mean CH50 activity level in COVID-19 patients is significantly reduced compared to healthy individuals [15].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The finding also match earlier findings by Ghazavi et al, which showed that C3 and C4 levels were markedly decreased in severe COVID-19 patients in comparison with non-severe COVID-19 patients [8]. In agreement with our data, Keshavarz et al indicated that mean CH50 activity level in COVID-19 patients is significantly reduced compared to healthy individuals [15].…”
Section: Discussionsupporting
confidence: 93%
“…However, this study supports the findings from previous observations [6,8,15]. Fang et al in a retrospective cohort study investigated C3 levels in COVID-19 patients [6].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Of note, it was shown that up-regulation of C1s led to host cell damage via the classical pathway in a model of SARS-CoV-2 infection ( 59 ). Clinical investigation found that the mean 50% hemolytic complement (CH50) level in COVID-19 patients was significantly lower compared to that in healthy individuals, likely due to sustained CP activation in these SARS-CoV-2 infected patients ( 60 ). Further studies found that antibody-mediated increase of CP activation was highly associated to COVID-19 disease severity ( 61 ), although the downstream effects of this activation may differ depending the disease status of the individual and on the specific antigen targeted ( 62 ).…”
Section: Infectious Diseasesmentioning
confidence: 99%
“…In severe cases, SARS-CoV-2 induces a dysregulated immune response that becomes detrimental to the host, described as ‘cytokine storm’ or ‘cytokine release syndrome’[ 7 ]. During cytokine storm, serum levels of complement components 3 and 4 (C3 and C4) and other components of the classical complement pathway as measured by the CH50 assay are decreased due to increased complement factor consumption[ 8 ]. Post-mortem cadaveric analysis of patients with severe SARS-CoV-2 infection has demonstrated thrombotic microangiopathy (TMA) implicating the activation of the complement cascade[ 9 ].…”
Section: Introductionmentioning
confidence: 99%